Bistable electrochromic device
By using electrolytes with specific ratios in bistable electrochromic devices, including polymer molecules, electrochromic materials and bromide ion-containing redox substances, to form aggregates to prolong fading time, the problems of material stability and cost in the prior art are solved, and efficient bistable performance is achieved.
Patent Information
- Application Number
- CN202510151710.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-25
AI Technical Summary
The existing bistable electrochromic materials have hindered the commercial development of bistable electrochromic devices due to high cost, poor bist stability and limited optical contrast.
An electrolyte is provided, including polymer molecules, electrochromic materials, bromide ion-containing redox substances, 1-butyl-3-methylimidazole tetrafluoroborate ionic liquid, photoinitiator and solvent. By combining these components, aggregates are formed to inhibit the self-erase reaction and prolong the fading time of the electrochromic material.
It improves the stability of electrochromic materials, extends the fading time of the device, ensures the performance of bistable electrochromic devices, and promotes its commercial application.
Smart Images

Figure CN119882313A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bistable electrochromic materials, and in particular to a bistable electrochromic device. Background Art
[0002] Bistable displays are considered to be the most promising solution to the high energy consumption of electronic displays because they can retain display information without consuming power. Reported bistable display strategies include liquid crystal, electronic ink, and electrochromic technology. Among them, bistable electrochromic devices undergo redox reactions under the action of an electric field to change the color of the device. Compared with other methods, they have certain advantages in terms of simple structure and ease of manufacture. Although various bistable electrochromic materials have been developed, such as inorganic materials, conjugated polymers, and fuel derivatives, their high cost, poor bistability, and limited optical contrast have hindered the commercial development of the devices. Therefore, how to improve the stability of electrochromic materials, inhibit the influence of diffusion on the color-changing molecules, and develop an economical, effective, and easy-to-prepare electrochromic system are the key to promoting the application of bistable electrochromic technology. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a bistable electrochromic device. The electrolyte of the present invention has excellent bistable performance.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The invention provides an electrolyte comprising polymer molecules, electrochromic materials, bromide ion-containing redox substances, 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, a photoinitiator and a solvent.
[0006] Preferably, the mass percentage of polymer molecules in the electrolyte is 10 to 30%;
[0007] The mass percentage of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid in the electrolyte is 10-40%;
[0008] The mass percentage of the photoinitiator in the electrolyte is 0.2-0.4%.
[0009] Preferably, the molar concentration of the electrochromic material in the electrolyte is 5 to 30 mmol / L;
[0010] The molar concentration of the bromide ion redox substance in the electrolyte is 5 to 30 mmol / L.
[0011] Preferably, the polymer molecules include one or more of polyacrylamide, polyacrylamide prepolymer, polyethylene oxide, polyethylene oxide prepolymer, polyacrylic acid, and polyacrylic acid prepolymer.
[0012] Preferably, the electrochromic material includes one or more of 1,1'-dipentyl-4,4'-bipyridinium dibromide, 1,1'-diheptyl-4,4'-bipyridinium dibromide and 1,1'-dinonyl-4,4'-bipyridinium dibromide.
[0013] Preferably, the bromide ion-containing redox substance includes one or more of lithium bromide, potassium bromide and sodium bromide.
[0014] The present invention also provides a method for preparing the electrolyte described in the above technical solution, comprising the following steps:
[0015] The polymer molecules, 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, a photoinitiator and a solvent are mixed to obtain a precursor;
[0016] The precursor, the electrochromic material and the bromide ion-containing redox substance are mixed to obtain the electrolyte.
[0017] The present invention also provides the use of the electrolyte described in the above technical solution or the electrolyte prepared by the preparation method described in the above technical solution in a bistable electrochromic device.
[0018] The present invention also provides a bistable electrochromic device, comprising a transparent conductive glass, a gel electrolyte layer and a counter electrode layer stacked in sequence;
[0019] The gel electrolyte layer is prepared from the electrolyte described in the above technical solution or the electrolyte prepared by the preparation method described in the above technical solution.
[0020] Preferably, the material of the transparent conductive glass is FTO or IT.
[0021] The present invention provides an electrolyte, comprising polymer molecules, an electrochromic material, a bromide ion redox substance, a 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, a photoinitiator and a solvent. The electrochromic material in the electrolyte of the present invention and the bromide ion redox substance will undergo a redox reaction to form aggregates under the condition of applying a voltage. The formation of the aggregates will inhibit the occurrence of a self-erasing reaction, thereby slowing down the fading time of the electrochromic material, improving the stability of the electrochromic material, helping the device to display continuously, and ensuring the performance of a bistable electrochromic device. The polymer molecules in the electrolyte ensure the uniformity of the distribution of the aggregates, extend the fading time of the device, and ensure the performance of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic diagram of the preparation process of the bistable electrochromic device described in Example 1;
[0023] Figure 2 Schematic diagram of the structure of the bistable electrochromic device prepared in Examples 1 to 7;
[0024] Figure 3 is the fading time of the bistable electrochromic devices described in Examples 1, 4 and 5;
[0025] Figure 4 is the fading time of the bistable electrochromic devices described in Examples 1, 6 and 7;
[0026] Figure 5 is a curve showing a change in transmittance of the bistable electrochromic device described in Example 1 as a function of applied voltage;
[0027] Figure 6 is the fading time of the bistable electrochromic device described in Example 1 after a constant voltage of 1.5 V is applied for 40 seconds;
[0028] Figure 7 This is a physical picture of the pattern change over time of the bistable electrochromic device described in Example 1 after patterning. DETAILED DESCRIPTION
[0029] The invention provides an electrolyte comprising polymer molecules, electrochromic materials, bromide ion-containing redox substances, 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, a photoinitiator and a solvent.
[0030] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0031] In the present invention, the mass percentage of the polymer molecules in the electrolyte is preferably 10-30%, more preferably 15-25%, and most preferably 18-22%. In an embodiment of the present invention, the mass percentage of the polymer molecules in the electrolyte may be 20%, 10% or 30%. In the present invention, the polymer molecules preferably include one or more of polyacrylamide, polyacrylamide prepolymer, polyethylene oxide, polyethylene oxide prepolymer, polyacrylic acid, and polyacrylic acid prepolymer, more preferably polyacrylamide, polyethylene oxide or polyacrylic acid; when the polymer molecules are two or more of the above-mentioned specific selections, the present invention does not have any special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0032] In the present invention, the type and content of the polymer molecules in the electrolyte are controlled within the above range to ensure the initial transmittance of the electrochromic device and to enable the polymer molecules in the electrochromic device to effectively inhibit the diffusion of aggregates. If the content of the polymer molecules exceeds 30%, due to the increase in microphase separation of the polymer molecules, strong light scattering occurs, which reduces the initial transmittance of the device and limits its practical application in displays, electrochromic windows, etc. If the content of the polymer molecules is less than 10%, it will cause the chemical cross-linking to fail, and the hydrogel will not be fully or even unable to form to inhibit the diffusion of aggregates, and the bistable performance of the device will be greatly reduced.
[0033] In the present invention, the molar concentration of the electrochromic material in the electrolyte is preferably 5 to 30 mmol / L, more preferably 15 to 25 mmol / L, and most preferably 18 to 22 mmol / L. In an embodiment of the present invention, the molar concentration of the electrochromic material in the electrolyte may be 15 mmol / L or 5 mmol / L. In the present invention, the electrochromic material preferably includes one or more of 1,1'-dipentyl-4,4'-bipyridinium dibromide, 1,1'-diheptyl-4,4'-bipyridinium dibromide and 1,1'-dinonyl-4,4'-bipyridinium dibromide, more preferably 1,1'-dipentyl-4,4'-bipyridinium dibromide, 1,1'-diheptyl-4,4'-bipyridinium dibromide or 1,1'-dinonyl-4,4'-bipyridinium dibromide; when the electrochromic material is two or more of the above-mentioned specific selections, the present invention has no special limitation on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0034] In the present invention, when the content of the electrochromic material exceeds 30 mmol / L, the transmittance difference of the electrochromic device is too high, resulting in waste of resources and increased costs; when it is lower than 5 mmol / L, the transmittance difference of the electrochromic device is insufficient, limiting its application range.
[0035] In the present invention, the molar concentration of the bromide ion redox substance in the electrolyte is preferably 5 to 30 mmol / L, more preferably 10 to 25 mmol / L, and most preferably 15 to 20 mmol / L. In an embodiment of the present invention, the molar concentration of the bromide ion redox substance in the electrolyte may be 15 mmol / L. In the present invention, the bromide ion redox substance preferably includes one or more of lithium bromide, potassium bromide and sodium bromide, more preferably lithium bromide; when the bromide ion redox substance is two or more of the above-mentioned specific selections, the present invention does not have any special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0036] In the present invention, when the content of the bromide ion-containing redox substance exceeds 30 mmol / L, the bistable performance is sufficient, resulting in waste of resources and increased costs; when it is lower than 5 mmol / L, the bistable performance of the device is insufficient, limiting its scope of application.
[0037] In the present invention, the mass percentage of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid in the electrolyte is preferably 10-40%, more preferably 15-35%, and most preferably 20-30%. In an embodiment of the present invention, the mass percentage of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid in the electrolyte can be 20%.
[0038] In the present invention, the 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid has the function of increasing the conductivity of the gel and improving the electrochemical window of the electrolyte.
[0039] In the present invention, the mass percentage of the photoinitiator in the electrolyte is preferably 0.2-0.4%, more preferably 0.2%. In the present invention, the photoinitiator preferably includes one or more of photoinitiator 2959, photoinitiator 1173 and photoinitiator 184, more preferably photoinitiator 2959.
[0040] In the present invention, the solvent preferably includes one or more of water, acetonitrile, ethanol and dimethylformamide, and more preferably water. When the solvent is two or more of the above-mentioned specific selections, the present invention has no special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0041] In the present invention, after the electrolyte is applied to the bistable electrochromic device, the electrochromic material therein can be made to form aggregates by applying voltage to prolong its fading time, and the color and fading time of the bistable electrochromic device can be adjusted by further regulating the alkyl chain length and the concentration of polymer molecules in the electrochromic material.
[0042] The present invention also provides a method for preparing the electrolyte described in the above technical solution, comprising the following steps:
[0043] The polymer molecules, 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, a photoinitiator and a solvent are mixed to obtain a precursor;
[0044] The precursor, the electrochromic material and the bromide ion-containing redox substance are mixed to obtain the electrolyte.
[0045] The invention mixes polymer molecules, 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, a photoinitiator and a solvent to obtain a precursor.
[0046] In the present invention, the mixing is preferably performed by adding polymer molecules, 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid and photoinitiator to the solvent and then heating and stirring. The present invention does not have any special restrictions on the order of adding the polymer molecules, 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid and photoinitiator. In the present invention, the temperature of the heating and stirring is preferably 60-80°C, more preferably 65-75°C, and most preferably 70°C; the stirring rate of the heating and stirring is preferably 400-1000rpm, more preferably 800-1000rpm, and most preferably 800rpm; the time of the heating and stirring is preferably 1-5h, more preferably 3-5h, and most preferably 3h.
[0047] After the heating and stirring are completed, the present invention also preferably includes cooling. The present invention does not have any special limitation on the cooling process. It can be carried out using a process well known to those skilled in the art and ensuring that the temperature after cooling reaches room temperature.
[0048] After obtaining the precursor, the present invention mixes the precursor, the electrochromic material and the bromide ion-containing redox substance to obtain the electrolyte.
[0049] In the present invention, the mixing preferably includes adding the electrochromic material and the bromide ion redox material to the precursor and then stirring. In the present invention, the stirring is preferably carried out under the conditions of protective atmosphere and stirring, and the protective atmosphere is preferably a nitrogen atmosphere or a helium atmosphere. In the present invention, the stirring speed is preferably 1200-1300rpm, more preferably 1200-1300rpm, and most preferably 1200rpm; the stirring time is preferably 0.2-1h, more preferably 0.3-0.6h, and most preferably 0.3h.
[0050] The present invention also provides the use of the electrolyte described in the above technical solution or the electrolyte prepared by the preparation method described in the above technical solution in a bistable electrochromic device.
[0051] The present invention also provides a bistable electrochromic device, comprising a transparent conductive glass, a gel electrolyte layer and a counter electrode layer stacked in sequence;
[0052] The gel electrolyte layer is prepared from the electrolyte described in the above technical solution or the electrolyte prepared by the preparation method described in the above technical solution.
[0053] In the present invention, the material of the transparent conductive glass is preferably FTO or ITO, more preferably FTO. In the present invention, the thickness of the transparent conductive glass is preferably 1.1 to 2.2 mm, more preferably 1.5 mm.
[0054] In the present invention, the thickness of the gel electrolyte layer is preferably 30 to 100 μm, more preferably 50 to 70 μm.
[0055] In the present invention, the material of the counter electrode layer is preferably one or more of platinum, cobalt sulfide and poly(3,4-ethylenedioxythiophene) (PEDOT), more preferably platinum. In the present invention, the thickness of the counter electrode layer is preferably 1 to 5 μm, more preferably 3 μm.
[0056] In an embodiment of the present invention, the effective area of the bistable electrochromic device may be 5.25 cm 2 .
[0057] In the present invention, the method for preparing the bistable electrochromic device preferably comprises the following steps:
[0058] A counter electrode layer is prepared on a transparent conductive glass by coating, and the transparent conductive glass and the counter electrode layer are separated by a "U"-shaped polymer spacer;
[0059] After the electrolyte is injected between the transparent conductive glass and the counter electrode layer, packaging and UV curing are performed in sequence to obtain the bistable electrochromic device.
[0060] The present invention adopts a coating method to prepare a counter electrode layer on a transparent conductive glass, and the transparent conductive glass and the counter electrode layer are separated by a "U"-shaped polymer gasket.
[0061] Before the coating, the present invention preferably pre-treats the transparent conductive glass, and the pre-treatment preferably includes cleaning and ultraviolet ozone treatment performed in sequence; the present invention does not have any special limitation on the cleaning and ultraviolet ozone treatment processes, and the processes familiar to those skilled in the art can be used.
[0062] After the pretreatment is completed, the present invention preferably places the polymer spacer on the surface of the transparent conductive glass before preparing the electrode layer. In the present invention, the thickness of the polymer spacer is preferably 30 to 60 μm. The polymer spacer is preferably a surin film.
[0063] In the present invention, the coating method is preferably spin coating. The present invention does not have any special limitation on the spin coating process, and it can be carried out using a process familiar to those skilled in the art. In an embodiment of the present invention, the spin coating process can be to spin-coat a chloroplatinic acid solution with a concentration of 15 to 25 mmol / L on the surface of the transparent conductive glass, and then heat and decompose to obtain the counter electrode layer. In the present invention, the concentration of the chloroplatinic acid solution is more preferably 20 to 23 mmol / L; the spin coating speed can be 7000 rpm, and the time can be 30 s; the temperature of the heating decomposition can be 300°C, and the time can be 3 min.
[0064] After obtaining the counter electrode layer, the present invention injects the electrolyte between the transparent conductive glass and the counter electrode layer, and then performs packaging and UV curing in sequence to obtain the bistable electrochromic device.
[0065] The present invention does not have any special limitation on the injection process, and the injection process may be performed using a process well known to those skilled in the art.
[0066] In the present invention, the packaging is preferably performed using UV curing adhesive. The present invention does not have any special limitation on the specific process of the packaging, and the packaging can be performed using a process well known to those skilled in the art.
[0067] In the present invention, the wavelength of the ultraviolet lamp used for the UV curing is preferably 365 nm, and the time of the UV curing is preferably 100 to 300 min, more preferably 100 to 200 min.
[0068] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0069] Example 1
[0070] like Figure 1The preparation process shown is as follows: after adding acrylamide monomer, 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid and photoinitiator 2959 to water, heating and stirring (the heating and stirring temperature is 70°C, the rotation speed is 800 rpm, and the time is 3 hours), after cooling to room temperature, 1,1'-diheptyl-4,4'-bipyridinium dibromide electrochromic material and lithium bromide are added, and stirring is carried out in a nitrogen atmosphere (the stirring speed is 800 rpm, and the time is 0.3 hours) to obtain an electrolyte (the mass percentage content of acrylamide monomer in the electrolyte is 20%, the mass percentage content of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid is 20%, the mass percentage content of the photoinitiator is 0.2%, the concentration of 1,1'-diheptyl-4,4'-bipyridinium dibromide electrochromic material is 15 mmol / L, and the concentration of lithium bromide is 15 mmol / L);
[0071] After washing and UV-ozone treating FTO transparent conductive glass with a thickness of 1.5 mm in sequence, a 50 μm thick sarling film is placed on the surface of the FTO transparent conductive glass, and then a 20 mmol / L chloroplatinic acid solution is spin-coated (rotation speed is 7000 rpm, time is 30 s) on the surface of the transparent conductive glass, and then heated and decomposed (temperature is 300° C., time is 3 min) to obtain the counter electrode layer (material is platinum, thickness is 3 μm);
[0072] After the electrolyte was injected between the FTO transparent conductive glass and the counter electrode layer, the device was encapsulated with UV curing glue and irradiated with a UV lamp with a wavelength of 365 nm for 100 min to obtain the bistable electrochromic device (effective area of 5.25 cm 2 ).
[0073] Example 2
[0074] Refer to Example 1, except that the acrylamide monomer is replaced by polyethylene oxide.
[0075] Example 3
[0076] Refer to Example 1, except that the acrylamide monomer is replaced by an acrylic acid monomer.
[0077] Example 4
[0078] Refer to Example 1, except that the mass percentage of acrylamide monomer in the electrolyte is 10%.
[0079] Example 5
[0080] Refer to Example 1, the difference is that the mass percentage of acrylamide monomer in the electrolyte is 30%.
[0081] Example 6
[0082] Refer to Example 1, except that the electrochromic material is replaced by 1,1'-dipentyl-4,4'-bipyridinium dibromide.
[0083] Example 7
[0084] Refer to Example 1, except that the electrochromic material is replaced by 1,1'-dinonyl-4,4'-bipyridinium dibromide.
[0085] Figure 2 This is a schematic diagram of the structure of the bistable electrochromic device prepared in Examples 1 to 7. A bias voltage is applied across the electrodes, a reduction reaction of viologen occurs at the working electrode, an oxidation reaction of bromide ions occurs at the counter electrode, the dicationic viologen is reduced to a monovalent cation radical, and the color of the device changes. In addition, the electrochromic material undergoes a redox reaction with the redox substance after voltage is applied, and aggregates are formed in the gel due to its reduced solubility.
[0086] Test Case
[0087] The transmittance of the bistable electrochromic devices prepared in Examples 1 to 3 was tested at a bias voltage of 1.5 V using an optical test system to obtain the fading time of the bistable electrochromic devices; Table 1 shows the transmittance, coloring time and fading time of the bistable electrochromic devices in Examples 1 to 3. It can be seen from Table 1 that the combination of the electrochromic material and the bromide ion-containing redox substance pair effectively prolongs the fading time of the device, and the formation of aggregates is an effective method to improve the bistable performance of the viologen electrochromic device, and the polymer molecules regulate the aggregates, among which polyacrylamide is the most preferred;
[0088] Table 1 Transmittance, coloring time and fading time of the bistable electrochromic devices described in Examples 1, 2 and 3
[0089] Initial transmittance Poor transmittance Coloring time Fading time Example 1 72.3% 56.7% 18s 8.91h Example 2 73.8% 58.2% 11s 3.54h Example 3 73.5% 57.0% 10.6s 0.57h
[0090] The transmittance of the bistable electrochromic devices prepared in Examples 1, 4 and 5 was tested at a bias voltage of 1.5 V using an optical testing system to obtain the fading time of the bistable electrochromic devices; wherein Figure 3 is the fading time of the bistable electrochromic devices described in Examples 1, 4 and 5, Figure 3 It can be seen that the content of the polymer molecules has an influence on the fading time of the bistable electrochromic device, wherein when the polymer molecules are polyamide, the content is optimal when it is 20%;
[0091] The transmittance of the bistable electrochromic devices prepared in Examples 1, 6 and 7 was tested at a bias voltage of 1.5 V using an optical testing system to obtain the fading time of the bistable electrochromic devices; wherein Figure 4 is the fading time of the bistable electrochromic devices described in Examples 1, 6 and 7, Figure 4 It can be seen that as the size of the electrochromic material (the length of the carbon chain) increases, the fading time of the bistable electrochromic device increases;
[0092] A steady-state voltage is applied to the bistable electrochromic device described in Example 1 using an electrochemical workstation, and the transmittance of the bistable electrochromic device is tested to obtain a curve showing the change of the transmittance of the bistable electrochromic device with the applied voltage, wherein Figure 5 is a curve showing the change of transmittance of the bistable electrochromic device as a function of applied voltage described in Example 1, Figure 5 It can be seen that the color change voltage of the bistable electrochromic device described in Example 1 is 1.5V;
[0093] After a constant voltage of 1.5 V was applied to both ends of the bistable electrochromic device described in Example 1 for 40 seconds, the fading time of the bistable electrochromic device was tested, wherein Figure 6 is the fading time of the bistable electrochromic device described in Example 1 after applying a constant voltage of 1.5 V for 40 seconds, Figure 6 It can be seen that the transmittance only decreased by 8% during the bistable electrochromic period of 966 s;
[0094] Figure 7 This is a physical picture of the pattern change of the bistable electrochromic device described in Example 1 over time after patterning. Figure 7 It can be seen that the bistable electrochromic device can be patterned;
[0095] Combination Figures 3 to 7 It can be seen that the bistable electrochromic device of the present invention has high stability ( Figure 3 ), high transmittance difference ( Figure 4 ), lower drive voltage ( Figure 5 ), excellent bistable performance ( Figure 6 ) and patternable ( Figure 7 ) and other advantages.
[0096] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that: The invention comprises polymer molecules, electrochromic materials, redox substances containing bromide ions, 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquids, photoinitiators and solvents.
2. The electrolyte according to claim 1, characterized in that The mass percentage of polymer molecules in the electrolyte is 10-30%; The mass percentage of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid in the electrolyte is 10-40%; The mass percentage of the photoinitiator in the electrolyte is 0.2-0.4%.
3. The electrolyte according to claim 1 or 2, characterized in that The molar concentration of the electrochromic material in the electrolyte is 5 to 30 mmol / L; The molar concentration of the bromide ion redox substance in the electrolyte is 5 to 30 mmol / L.
4. The electrolyte according to claim 3, characterized in that The polymer molecules include one or more of polyacrylamide, polyacrylamide prepolymer, polyethylene oxide, polyethylene oxide prepolymer, polyacrylic acid, and polyacrylic acid prepolymer.
5. The electrolyte according to claim 3, characterized in that The electrochromic material includes one or more of 1,1'-dipentyl-4,4'-bipyridinium dibromide, 1,1'-diheptyl-4,4'-bipyridinium dibromide and 1,1'-dinonyl-4,4'-bipyridinium dibromide.
6. The electrolyte according to claim 3, characterized in that The bromide ion-containing redox material includes one or more of lithium bromide, potassium bromide and sodium bromide.
7. The method for preparing the electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: The polymer molecules, 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, a photoinitiator and a solvent are mixed to obtain a precursor; The precursor, the electrochromic material and the bromide ion-containing redox substance are mixed to obtain the electrolyte.
8. Use of the electrolyte according to any one of claims 1 to 6 or the electrolyte prepared by the preparation method according to claim 7 in a bistable electrochromic device.
9. A bistable electrochromic device, characterized in that: It includes a transparent conductive glass, a gel electrolyte layer and a counter electrode layer which are stacked in sequence; The gel electrolyte layer is prepared from the electrolyte according to any one of claims 1 to 6 or the electrolyte prepared by the preparation method according to claim 7.
10. The bistable electrochromic device according to claim 9, characterized in that: The material of the transparent conductive glass is FTO or ITO.